2009
DOI: 10.1186/1756-3305-2-47
|View full text |Cite
|
Sign up to set email alerts
|

Blood feeding by the Rocky Mountain spotted fever vector, Dermacentor andersoni, induces interleukin-4 expression by cognate antigen responding CD4+ T cells

Abstract: Background: Tick modulation of host defenses facilitates both blood feeding and pathogen transmission. Several tick species deviate host T cell responses toward a Th2 cytokine profile. The majority of studies of modulation of T cell cytokine expression by ticks were performed with lymphocytes from infested mice stimulated in vitro with polyclonal T cell activators. Those reports did not examine tick modulation of antigen specific responses. We report use of a transgenic T cell receptor (TCR) adoptive transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…This component explained 47% of the variation in macroparasite burden and showed high positive loadings for all three macroparasite groups (ticks: 0.56, fleas: 0.57 and adult cestodes: 0.60). Grouping of ectoparasites and endoparasites in this way is in line with previous work that shows that both ectoparasites (Boppana, Thangamani, Adler, & Wikel, ; Boppana, Thangamani, Alarcon‐Chaidez, Adler, & Wikel, ) and endoparasites (Anthony et al., ; Harris & Gause, ) stimulate the Th2 response, which has been suggested to be a mechanism for adaptive and rapid tissue repair against parasite‐induced damage (Allen & Wynn, ). These variables have previously been identified as important predictors of Gata3 expression (Jackson et al., , ).…”
Section: Methodssupporting
confidence: 88%
“…This component explained 47% of the variation in macroparasite burden and showed high positive loadings for all three macroparasite groups (ticks: 0.56, fleas: 0.57 and adult cestodes: 0.60). Grouping of ectoparasites and endoparasites in this way is in line with previous work that shows that both ectoparasites (Boppana, Thangamani, Adler, & Wikel, ; Boppana, Thangamani, Alarcon‐Chaidez, Adler, & Wikel, ) and endoparasites (Anthony et al., ; Harris & Gause, ) stimulate the Th2 response, which has been suggested to be a mechanism for adaptive and rapid tissue repair against parasite‐induced damage (Allen & Wynn, ). These variables have previously been identified as important predictors of Gata3 expression (Jackson et al., , ).…”
Section: Methodssupporting
confidence: 88%
“…In addition, we observed higher mRNA levels of IL‐10 in tick‐infested mice, although the difference was not statistically significant. This finding has been observed previously in studies in which concomitant increases in the Th2 cytokine IL‐10 in the spleen of C3H/HeJ mice were examined under different conditions of infection (Zeidner et al ., ; Ferreira & Silva, ; Boppana et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the transcription factor GATA‐binding factor 3 (Gata3) in mitogen‐stimulated splenocytes was found to mark both tolerant animals (amongst mature males) and resistant animals (amongst immature males) in the cross‐sectional set. Furthermore, analyses of time‐lagged associations in mature males in the longitudinal data suggested that macroparasite infections triggered Gata3 responses [as might be expected in laboratory models ], which in turn gave rise to increases in body condition. This corroborated the cross‐sectional analyses and supported a hypothesis that Gata3 activity stimulated by macroparasites is part of a complex of (tolerance) responses leading to the readjustment of body condition in mature males.…”
Section: Case Studies: Two Recent Focuses On Naturally Occurring Nonmmentioning
confidence: 78%